2015
DOI: 10.1080/09593330.2015.1079264
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of toxicity and biodegradability on activated sludge of priority and emerging pollutants

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in: El acceso a la versión del editor puede requerir la suscripción del recurso Access to the published version may require subscription

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 50 publications
(46 reference statements)
1
14
1
Order By: Relevance
“…The toxicity of the Fenton effluent was assessed through the Microtox ® assay, which was used previously with various pesticides . Figure also shows the IC 50 values (TU) of the effluents from Fenton‐like oxidation at different H 2 O 2 doses.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The toxicity of the Fenton effluent was assessed through the Microtox ® assay, which was used previously with various pesticides . Figure also shows the IC 50 values (TU) of the effluents from Fenton‐like oxidation at different H 2 O 2 doses.…”
Section: Resultssupporting
confidence: 93%
“…The toxicity of the Fenton effluent was assessed through the Microtox ® assay, which was used previously with various pesticides. 36 Figure 3 also shows the IC 50 values (TU) of the effluents from Fenton-like oxidation at different H 2 O 2 doses. The assay revealed that a 25% H 2 O 2 dose dramatically decreased the luminescence of the effluent from Fenton oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MDA and 4-hydroxynonenal are biomarkers of lipid peroxidation (Demir et al, 2011), attacking distant targets and covalently binding with biomolecules (Levent et al, 2006). Reduction in MDA level in rats co-treated with quercetin indicates its ability to protect against DCM mediated lipid peroxidation, due to its antioxidant activity (Xiao et al, 2018). DCM treatment also resulted in decreased hepatorenal antioxidant enzymes (SOD, CAT, GPx), essential for superoxide radical biotransformation to H 2 O 2, thus preventing its damaging effects (Klaunig et al, 2011) on one hand and cytotoxicity by transforming H 2 O 2 to water and oxygen (Kohen & Nyska, 2002;Adedara et al, 2012) on the other hand.…”
Section: Discussionmentioning
confidence: 99%
“…Acute and chronic exposure to DCM reportedly poses great threat to humans and ecosystems due to its toxicity, persistence, and bioaccumulation in the food chain (Tobajas et al, 2016). DCM, due to its lipophilicity is easily absorbed and metabolized in humans and animals resulting in multiple organ damage (Schlosser et al, 2015).…”
Section: Introductionmentioning
confidence: 99%